Electronic Mind Mapping: Promote Students’ Engagement in Speaking-Based Activities - Noni Agustina (Edu-Ling: Journal of English Education and Linguistics, 2018)
This study aims to explore deeply on the use of electronic mind mapping in order to promote students’ engagement in English class, especially in speaking-based activities. The method used was descriptive qualitative with purposive sampling. The instruments for collecting data were class observation, interview, and questionnaire sheets (triangulation technique). The participant was first graders of 89 Junior High School, Jakarta. The finding showed that the use of electronic mind mapping gave the benefit to students’ speaking activities. They had effective, behavior and cognitive engagement when doing their tasks in using electronic mind mapping. They had a positive perception of using that application because they had new knowledge of it, high learning motivation and participate actively in learning.